Hospital volume of throughput and periprocedural and medium-term adverse events after percutaneous coronary intervention: retrospective cohort study of all 17 417 procedures undertaken in Scotland, 1997–2003. Issue 11 (18th May 2006) - Burton, K R; Slack, R; Oldroyd, K G; Pell, A C H; Flapan, A D; Starkey, I R; Eteiba, H; Jennings, K P; Northcote, R J; Hillis, W Stewart; Pell, J P
Abstract : Objective: To determine whether percutaneous coronary intervention (PCI) hospital volume of throughput is associated with periprocedural and medium-term events, and whether any associations are independent of differences in case mix. Design: Retrospective cohort study of all PCIs undertaken in Scottish National Health Service hospitals over a six-year period. Methods: All PCIs in Scotland during 1997–2003 were examined. Linkage to administrative databases identified events over two years' follow up. The risk of events by hospital volume at 30 days and two years was compared by using logistic regression and Cox proportional hazards models. Results: Of the 17 417 PCIs, 4900 (28%) were in low-volume hospitals and 3242 (19%) in high-volume hospitals. After adjustment for case mix, there were no significant differences in risk of death or myocardial infarction. Patients treated in high-volume hospitals were less likely to require emergency surgery (adjusted odds ratio 0.18, 95% confidence interval (CI) 0.07 to 0.54, p  =  0.002). Over two years, patients in high-volume hospitals were less likely to undergo surgery (adjusted hazard ratio 0.52, 95% CI 0.35 to 0.75, p  =  0.001), but this was offset by an increased likelihood of further PCI. There was no net difference in coronary revascularisation or in overall events. Conclusion: Death and myocardial infarction were infrequent complications of PCI and did not differ significantly by volume. Emergency surgery was less common in high-volume hospitals. Over two years, patients treated in high-volume centres were as likely to undergo some form of revascularisation but less likely to undergo surgery.